Pengembangan Media Little Picture Card (LPC) Materi Jamur Endofit Untuk Melatih Kemampuan Literasi Sains Mahasiswa Universitas KH. A. Wahab Hasbullah - Fariyanti, Ika; Meishanti, Ospa Pea Yuanita (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2023)
ABSTRACT One of the materials in the General Biology course is Fungi in the Biology Education Program of KH University. A. Wahab Hasbullah. The teaching lecturer stated that the Fungi material required practical activities, but practicum facilities were not yet available. These problems can be overcome with the Little Picture Card (LPC) learning media. LPC media contains material and pictures so that it can explain the meaning of the concepts being studied. Therefore, researchers will develop the Little Pictur Card (LPC) learning media for endophytic fungi. The research objectives were: (1) to describe the feasibility of Little Picture Card (LPC) media on endophytic mushroom material, (2) to describe the feasibility of Little Picture Card (LPC) media, (3) to describe student responses to the attractiveness of Little Picture Card media ( LPC) on endophytic fungal material. This study uses the ADDIE research model. The research procedure went through 5 stages, namely: 1) analysis 2) design 3) development 4) implementation and 5) evaluation. Media validation was carried out by material experts and media experts, while response validation was carried out by 21 Biology Education study program students. The results showed that the Little Picture Card media performed by material experts and media experts, material experts showed the criteria of